Results of Rock Magnetic and Mineralogical Analyses of Ultramafic Cores from the Oman Drilling Project - Hong, Gilbert (10997221); Till, Jessica Lynn (10997224); Greve, Annika (10814635); Lee, Sang-Mook (10997227) (2021)
This dataset comprises of original rock magnetic data, microscope images, and EDS reports used for analysis of serpentinized ultramafic cores drilled during the Oman Drilling Project (OmanDP). Rock magnetic experiments have been performed onboard D/V Chikyu and in a shielded facility located at the University of Iceland. Results included in the dataset are as follows: Mass susceptibility, Natural remanence before and after alternating field (AF) and thermal demagnetization, and thermomagnetic measurements. Microscopic images and EDS reports are the results of backscatter electron microscopy that was held at Seoul National University with a JEOL JSM-7100F scanning electron microscope.